(untitled) (Ameghiniana, 2013)
ABSTRACT: THE FIRST ISOTEMNIDAE(MAMALIAN, NOTOUNGULATA) KNOW FROM THE LUMBRERA FORMATION (SALTA GROUP). Pamaptemnus infernalis gen. et sp. nov. and P. deuteros sp. nov. are here described, based on cranial and mandibular remains obtained from the lowest part of the Lumbrera Formation (Salta Group, Santa Bárbara Subgroup) at Estancia Pampa Grande, province of Salta. They represent the first Isotemnidae from the Santa Bárbara Subgroup, and also the first unquestionable Isotemnidae recorded outside Patagonia. Pampatemnusinfernalis is morphologically eloser to Pleurostylodon and Anisotemnus from the Casamayoran Mammal-age of Patagonia, than to any other isotemnid genera known from other Land-Mammal ages. This fact is in accordance with the Casamayoran age assigned to the Lumbrera Formation on the evidence provided by the other marnmals recorded in it. The observed differences hetween the contemporaneous faunal assemblages of the Lumbrera Formation (Northwest Argentina, 210-24" S lat.) and those of the Gran Barranca member, Sarmiento Formation (Patagonia, 450_460 S. lat.) are here interpreted as indicators that both areas had somewhat different climates and environments during the early Eocene.